Implementation of PKN Learning Assessment in Covid-19 in Class IV of Al-Fauzi Elementary School - Andina Halimsyah Rambe; Annisa Khairah (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to determine the implementation of PKN learning assessment in the pandemic period in Class IV of Al-Fauzi Elementary School. This study is a qualitative descriptive study with the research subject of grade IV-A teacher of SDIT Al-Fauzi. Research data were obtained through interview techniques and documentation techniques. Then the data were analysed to get an overview of the implementation of PKN learning assessments in pandemic times. Based on research results showing the performance of PKN learning assessment in the pandemic period in Class IV of Al-Fauzi Elementary School conducted online through WhatsApp and face-to-face through home visit application. PKN learning assessment activities are carried out by giving questions in the form of objective tests, i.e., multiple-choice tests and essay tests, to students who are then conducted assessments by teachers. The impediment to the implementation of PKN learning assessment in pandemic times is that the mobile phone used by the teacher had experienced errors due to a large number of photos of students' assignments to be assessed.